(untitled) (Research, Society and Development, 2020)
The creation of free-range chicken is characterized as a predominantly domestic production, due to its rusticity and, also, by the production format itself, where the animals live free and feed on alternative sources present in the place. The objective of this review article was to verify the scientific production on the theme of chicken and free-range / colonial chicken by means of qualitative and quantitative analysis of indexed articles, using the Scientific Electronic Electronic Library Online (Scielo) as a database. Data collection was carried out through bibliometric analysis, with the measurement of scientific production on these themes in the last 20 years. 26 articles by Brazilian authors were analyzed from 1999 to 2018, 19 articles published in Portuguese and 7 in English. The Qualis of the journals analyzed was also checked by consulting the Sucupira Platform of the Coordination for the Improvement of Higher Education Personnel (Capes), with a predominance of the B1 and B2 classification scope, based on the Agrarian Sciences evaluation area I. The analysis and the interpretation of the data allowed the identification of journals with a greater volume of publications, in addition to authors with assiduous publications and their respective institutional affiliations. It was also clear that the subjects most frequently addressed in the journals are meat quality, health, nutrition and productive efficiency.